La psicología de la salud : antecedentes, definición y perspectivas (2010)
ABSTRACT: This paper proposes a critical reflection of the historical and theoretical foundation of psychology's applied field known as health psychology. Psichologist's role and funtion in this field is discussed, and some theoretical and methodological tools for this type of job are proposed, specifically for threes areas: primary care, management of health promotion and prevention projects, psycho-oncology, and the care of patients with aesthetic treatments.